"Darwin's corollary" and cytoplasmic incompatibility induced by Cardinium may contribute to speciation in Encarsia wasps (Hymenoptera: Aphelinidae). (1st November 2016) - Gebiola, Marco; Kelly, Suzanne E.; Hammerstein, Peter; Giorgini, Massimo; Hunter, Martha S.
Abstract: The potential importance of cytoplasmic incompatibility (CI)‐inducing bacterial symbionts in speciation of their arthropod hosts has been debated. Theoretical advances have led to a consensus that a role is plausible when CI is combined with other isolating barriers. However, the insect model systems Nasonia and Drosophila are the only two experimental examples documented. Here, we analyzed the components of reproductive isolation between the parasitoid wasp Encarsia suzannae, which is infected by the CI‐inducing symbiont Cardinium, and its uninfected sibling species Encarsia gennaroi . Laboratory crosses demonstrated that: (1) sexual isolation is incomplete; (2) hybrid offspring production is greatly reduced in the interspecific CI cross; (3) viable hybrids may be produced by curing E. suzannae males of Cardinium with antibiotics; (4) hybrid offspring production in the reciprocal cross is greatly reduced by hybrid inviability due to genetic incompatibilities; (5) hybrid sterility is nearly complete in both directions at the F1 stage. Thus, asymmetrical hybrid incompatibilities and CI act as complementary isolating mechanisms. We propose a new model for contributions of CI symbionts to speciation, with CI reducing gene flow between species in one direction, and in the other, a symbiont sweep resulting in accelerated mtDNA evolution, negative cytonuclear interactions, and hybrid incompatibilities.